Immobilization and Evaluation of Penicillin G Acylase on Hydroxy and Aldehyde Functionalized Magnetic α-Fe2O3/Fe3O4 Heterostructure Nanosheets - Ni, Yun; Lv, Zhixiang; Wang, Zhou; Kang, Shouyu; He, Dawei; Liu, Ruijiang (Frontiers in Bioengineering and Biotechnology, 2022)
Magnetic α-Fe2O3/Fe3O4 heterostructure nanosheets were fabricated via hydrothermal calcination. The activity of penicillin G acylase (PGA), which was covalently immobilized onto silica-decorated heterostructure nanosheets, achieved the highest activity of 387.03 IU/g after 18 h incubation with 0.1 mL PGA. In contrast, the activity of free PGA reached the highest level when the temperature was 45 °C with a pH of 8.0. However, the activity of free PGA changed more dramatically than immobilized PGA as the relative conditions changed. Moreover, the Michaelis-Menten constant (Km) and reusability of immobilized PGA were also explored. The results showed that free PGA Km and maximum rate (Vmax) were 0.0274 M and 1.167 μL/min, respectively. Km and Vmax values of immobilized PGA were 0.1082 M and 1.294 μL/min, respectively. After 12 cycles of repetitive use, immobilized PGA remained approximately 66% of its initial activity, indicating that the PGA immobilized onto the heterostructure nanosheets showed better stability and reusability than free PGA.